Influence of Special Needs Education Policy on Access to Secondary School Education By Learners With HearingImpairments In Nandi County, Kenya - Muhombe, Joseph Andrew; Rop, Naftali K; Ogola, Fredrick; Justus, Nyongesa Wesonga (My University, 2015)
This study sought to examine influence of Special Needs Education Policy on access to secondary schooleducation by learners with hearing impairments in Nandi County, Kenya. The study was informed by the Multiple Intelligences theory and the Dewey theory of Progressivism. The findings showed that majority of the respondents were aware of the Special Needs Education Policy Framework of 2009 and believed that the policy was being implemented. Majority of the respondents felt that the implementation of the policy had positively affected learners’ enrolment in schools but recognized that there were still several challenges that were acting as barriers to school access by learners with hearing impairments in Nandi County. Further, the respondents observed that the implementation of the Special Needs Education Policy had led to a slight improvement on transition of learners with hearing impairments from primary to secondary schools in Nandi County. Theinfluence of the Special Needs Education Policy on retention of learners with hearing impairments was deemed to be marginally small in schools in Nandi County. The results also showed that there were cases of learners dropping out of school because of a number of reasons including financial problems, lack of motivation to be in school and cultural factors, among others. In order to improve access to school education by learners with hearing impairments, respondents gave their opinions on how the challenges could be handled including the need to train more teachers to teach learners with hearing impairments, provision of adequate learning materials and the need to fund the special units/schools for the hearing impaired in the county, among others. The study recommends that the Government should set clear guidelines on how the Special Needs Education Policy can be implemented and coordinated. The study also recommends increase of necessary support for the secondary and primary school/units for the hearing impaired in the county so as to improve access to school education by children with hearing impairments.
Keywords: Special needs policy; Hearing impairment; Access to education